The Adiwiyata School's Role in the Development of Character Caring for the Environment (A Case Study at the Junior High School 6 Tuban) - Fadlillah, Umi; Ngabekti, Sri; Lisdiana, Lisdiana (Postgraduate, Universitas Negeri Semarang, Indonesia, 2018)
The nation moral condition was apprehensive especially the awareness to the environment aroused Indonesian government to instill caring culture and loving environment by applying Adiwiyata Program. The purpose of this research was to know: 1) The implementation Adiwiyata Program in Junior high school 6 Tuban post awarded as Adiwiyata Independent school/Sekolah Adiwiyata Mandiri, 2) The strategy development of environmental caring characteristic, 3) The obstacles that have been found 4) The effort to resolve the obstacles. This research used qualitative approach of case study types. The research procedure divided into four steps; preparing, implementing, analyzing and writing the research report. The result shown that Junior high school 6 Tuban still strive to preserve Adiwiyata post awarded program as Sekolah Adiwiyata Mandiri. Strategy development of environmentally caring character in Junior high school 6 Tuban was carried out based on four aspects of Adiwiyata Program implementation, but each aspect has not been implemented optimally. These aspects could be optimized with the consistency and commitment of the school community. This consistency was enhanced by positioning students as the center in the implementation of Adiwiyata Program and added role model, reward and punishment as an alternative strategy to increase motivation in developing students’ caring character.